Predictors of Outcomes After Focused Ultrasound Thalamotomy. Issue 2 (6th November 2019) - Krishna, Vibhor; Sammartino, Francesco; Cosgrove, Rees; Ghanouni, Pejman; Schwartz, Michael; Gwinn, Ryder; Eisenberg, Howard; Fishman, Paul; Chang, Jin Woo; Taira, Takaomi; Kaplitt, Michael; Rezai, Ali; et al.
Abstract: BACKGROUND: Magnetic resonance-guided focused ultrasound thalamotomy (FUS-T) is an emerging treatment for essential tremor (ET). OBJECTIVE: To determine the predictors of outcomes after FUS-T. METHODS: Two treatment groups were analyzed: 75 ET patients enrolled in the pivotal trial, between 2013 and 2015; and 114 patients enrolled in the postpivotal trials, between 2015 and 2016. All patients had medication-refractory, disabling ET, and underwent unilateral FUS-T. The primary outcome (hand tremor score, 32-point scale with higher scores indicating worse tremor) and the secondary outcome variables (Clinical Rating Scale for Tremor Part C score: 32-point scale with higher scores indicating more disability) were assessed at baseline and 1, 3, 6, and 12 mo. The operative outcome variables (ie, peak temperature, number of sonications) were analyzed. The results between the 2 treatment groups, pivotal and postpivotal, were compared with repeated measures analysis of variance and adjusted for confounding variables. RESULTS: A total of 179 patients completed the 12-mo evaluation. The significant predictors of tremor outcomes were patient age, disease duration, peak temperature, and number of sonications. A greater improvement in hand tremor scores was observed in the postpivotal group at all time points, including 12 mo (61.9% ± 24.9% vs 52.1% ± 24.9%, P = .009). In the postpivotal group, higher energy was used, resulting in higher peak temperatures (56.7 ± 2.5 vs 55.6 ± 2.8°C, P = .004). After adjusting for age, years of disease, number of sonications, and maximum temperature, the treatment group was a significant predictor of outcomes (F = 7.9 [1, 165], P = .005). CONCLUSION: We observed an improvement in outcomes in the postpivotal group compared to the pivotal group potentially reflecting a learning curve with FUS-T. The other associations of tremor outcomes included patient age, disease duration, peak temperature, and number of sonications.